PERANCANGAN KEMASAN SUSHI KEDAI MIE RAMEN GOR H. AGUS SALIM PADANG - FAJRI ILHAM, Dra. Zubaidah, M.Sn., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Sushi is one of the traditional food from Japan, made from rice and slices of fish meat. At the present time the meal can be found in the city of Padang, housed in GOR. H Agus Salim with outlets named is